Healable and shape editable supercapacitors based on shape memory polyurethanes. Issue 29 (9th July 2019) - Li, Tianqi; Fang, Xu; Pang, Qiang; Huang, Weimin; Sun, Junqi
Abstract : Healable and shape-editable supercapacitors can heal damage and be shape-edited to desired geometries with a negligible decay in the specific capacitance. Abstract : Flexible supercapacitors that can heal mechanical damage to improve their reliability and be repeatedly programmed into different geometries without sacrificing their specific capacitance are important for wearable electronics. In this study, healable and shape-editable supercapacitors are fabricated by sandwiching poly(acrylic acid)–poly(ethylene oxide) (PAA–PEO) hydrogel electrolytes between two pieces of carbon nanotube (CNT)-coated polyurethane–poly(ε-caprolactone) (PU–PCL) electrodes. The flexible, healable and shape-editable supercapacitor delivers a specific capacitance of ∼37 F g −1 at a scan rate of 0.5 A g −1 and exhibits an outstanding cycling performance with a capacitance retention of ∼96.5% after 10 000 charge/discharge cycles. Because of the healability of PU–PCL substrates and PAA–PEO hydrogel electrolytes, the fractured supercapacitors can heal physical damage and restore ∼92.6% of their original specific capacitance after 5 cutting/healing cycles upon heating at 75 °C. Moreover, benefiting from the shape memory ability of the PU–PCL substrates, the supercapacitors can be shape-edited to desired shapes with a high shape fixing and recovery ratio, and display a negligible decay in the specific capacitance during repeated shape-editing processes.